Mites as a Potential Path for Ce-Ti Exposure of Amphibians - Jacinto-Maldonado, Mónica; Meza-Figueroa, Diana; Pedroza-Montero, Martín; Lesbarrères, David; Robles-Morúa, Agustín; Navarro-Espinoza, Sofía; González-Grijalva, Belem; Pérez-Segura, Efrén; Silva-Campa, Erika; Angulo-Molina, Aracely; Paredes-León, Ricardo (Frontiers in Environmental Science, 2022)
Despite the documented effects on human and animal health, particles smaller than 0.1 µm in diameter found in soils, sediments, and the atmosphere remain unregulated. Yet, cerium and titanium oxide nanoparticles associated with traffic increase mortality, cause behavioral changes, and inhibit the growth in amphibians. Mites of the genus Hannemania spend their early stages in the soil before becoming exclusive parasites of amphibians. Unlike other mites, Hannemania is found inside the epidermis of amphibians, thus facilitating the intake of particles, and leading to direct and chronic exposure. To better understand this exposure path, we sampled amphibians hosting mites in a river potentially polluted by traffic sources. Particles collected from mites were studied by scanning electron microscopy and Raman spectroscopy while sediment samples were analyzed for total metal content by portable X-ray fluorescence. Our results indicate that sediment samples showed significant correlations between elements (Zr, Mn, Ti, Nb, Fe) often associated with components in catalytic converters and a level of Zr that exceeded the local geochemical background, thus suggesting an anthropic origin. Furthermore, particles adhered to mites exhibited the characteristic Raman vibrational modes of ceria (CeO2, 465 cm−1), ceria-zirconia (CeO2-ZrO2, 149, 251, and 314 cm−1), and rutile (TiO2, 602 cm−1), pointing out to the deterioration of catalytic converters as the most likely source. This research highlights both the importance of unregulated catalytic converters as a source of ultrafine Ce-Ti particle pollution and the role of sub-cutaneous mites as a vector of these particles for amphibian exposure.